Intertidal Seaweeds Modulate a Contrasting Response in Understory Seaweed and Microphytobenthic Early Recruitment - Umanzor, Schery; Ladah, Lydia; Zertuche-González, José A. (Frontiers in Marine Science, 2018)
Recruitment is a fundamental step upon which all subsequent interactions within a community occur. We explored how the attenuation of physical conditions by seaweed plots comprised of either Chondracanthus canaliculatus, Pyropia perforata, Sylvetia compressa or a mixed aggregation, at varying densities (average 1199, 816 and 408 in. m-2), affected recruitment of seaweeds and microphytobenthic organisms in the understory, and if physical factors modulate their abundance and distribution. We outplanted macroscopic seaweeds in the intertidal and measured changes in understory irradiance, particle retention, and bulk water flow. Both factors influenced physical conditions below the canopy. However, only canopy density had a significant effect on recruitment. The low-density treatments showed greater abundance of seaweeds, with the opposite found for microphytobenthic organisms. The recruitment processes of seaweeds and microphytobenthic organisms, however, appeared to be independent of each other and were not due to competition. We conclude that it is crucial to consider microscale biological interactions, which are rarely addressed when assessing recruitment processes of benthic primary producers.